Understanding Indian society: past and present - Baviskar, B. S (ed.); Patel , Tulsi (ed.) (Hyderabad, 2010)
Understanding Indian Society brings together a collection of writings by eminent scholars across disciplines that capture the dynamic character of Indian society. The fifteen essays focus on four vital areas-gender relations, religion, developmental concerns and social change, and the future of the disciline of sociology. The volume explores a wide range of issues as varied as Muslim women's struggle for independence in a patriarchal society, colonial linkages of female foeticide, religious and communal conflicts, dilemmas of practising medical ethics, participation of the Patidar diaspora in the prosperity of the Gujarati community, among others. Taken together, the collection demonstrates the analytical richness of current scholarship and gives fresh insights into the society of India. Commemorating Professor A. M. Shah's work in the contemporary context, the contributors highlight the major role he played in the growth of sociology as a discipline. The book will be of interest to specialists in gender studies, sociology of family and religon, medical socillogy and development studies. It will also appeal to readers interesed in the complex structure and practices of Indian society.
Keywords: Society-India